Not Just for Novices: The Programmatic Impact of Practice-Based Teacher Education. (3rd April 2018) - Francis, Anthony Tuf; Olson, Mark; Weinberg, Paul J.; Stearns-Pfeiffer, Amanda
ABSTRACT: This article describes how a secondary teacher education program at a midsized university made the turn toward a practice-based program in teacher education. The authors argue that efforts to recenter the program around practices have not only improved opportunities for novice teachers, but also have provided teacher educators a programmatic framework for making substantive progress toward three attributes of quality teacher education: increased collaboration between teacher educators, greater coherence between courses and experiences, and improved legitimacy of university-based teacher education. The authors detail specific components of this program reform and explain how such efforts have resulted in valuable gains across each attribute. The authors also explain how they implemented these programmatic changes largely within existing course and field-experience structures, and without substantive new infusions of personnel or funding.